Pengaruh Pemberian Ekstrak Etanol Daun Kersen (Muntingia calabura L.) terhadap Hiperurisemia Mencit Putih (Mus musculus) - Asan, Maria Ignatia De Loyola Ina Peni; Amat, Anita Lidesna Shinta; Kareri, Dyah Gita Rambu; Setianingrum, Elisabeth Levina Sari (JURNAL KAJIAN VETERINER, 2025)
Characterized by high uric acid concentrations, hyperuricemia is a condition that responds to both modern pharmaceutical interventions and herbal or folk remedies. Traditionally, uric acid levels reduction can be achieved by using cherry leaves (Muntingia calabura L.) which contain flavonoids, saponins, and tannins decreas of uric acid depends on the quality of the plant. East Nusa Tenggara, known for its arid conditions and different climatic characteristics, requires specific studies on how cherry leaves influence hyperuricemia in the region. This research aim to investigate the effect of Muntingia calabura L. (cherry leaf) extract on hyperuricemic Mus musculus (white mice). The study's methodology is a true experimental design, incorporating a pretest-post-test control group. This research involved a negative control, a positive control, and three treatment groups that received high-purine diets along with cherry leaf extract at doses of 13, 26, and 52 mg per 20 grams of body weight per day. Data were analyzed using normality test, homogenity test, paired samples t-test and one-way Anova which processed by using SPSS. A statistically significant difference was found, as evidenced by a p-value less than 0.05 from the paired samples t-test. Additionally, the One-Way ANOVA test showed a p-value of 0.005 (p<0.05), confirming a significant difference between the control and treatment groups. Research indicates that extracts from Muntingia calabura L. leaves may effectively lower uric acid concentrations in white mice suffering from hyperuricemia (Mus musculus).